Nano-vectors for efficient liver specific gene transfer - Atul Pathak (Dove Medical Press, 2008)
Atul Pathak1, Suresh P Vyas2, Kailash C Gupta11Nucleic Acids Research Laboratory, Institute of Genomics and Integrative Biology, Delhi University Campus, Delhi, India 2Department of Pharmaceutical Sciences, Dr. Harisingh Gour Vishwavidyalaya, Sagar, (M.P.), IndiaAbstract: Recent progress in nanotechnology has triggered the site specific drug/gene delivery research and gained wide acknowledgment in contemporary DNA therapeutics. Amongst various organs, liver plays a crucial role in various body functions and in addition, the site is a primary location of metastatic tumor growth. In past few years, a plethora of nano-vectors have been developed and investigated to target liver associated cells through receptor mediated endocytosis. This emerging paradigm in cellular drug/gene delivery provides promising approach to eradicate genetic as well as acquired diseases affecting the liver. The present review provides a comprehensive overview of potential of various delivery systems, viz., lipoplexes, liposomes, polyplexes, nanoparticles and so forth to selectively relocate foreign therapeutic DNA into liver specific cell type via the receptor mediated endocytosis. Various receptors like asialoglycoprotein receptors (ASGP-R) provide unique opportunity to target liver parenchymal cells. The results obtained so far reveal tremendous promise and offer enormous options to develop novel DNAbased pharmaceuticals for liver disorders in near future.Keywords: hepatocytes, nanoparticles, liposomes, nucleic acids, asialoglycoprotein receptors